Algorith for characterizing innovation agents in Mexico city - García-Jarquín , Brenda; Aguilar-Fernández, Mario; Salgado-Escobar, Graciela (Nexo Revista Científica, 2022)
Innovation and technological change are the engine of national competitiveness, economic development, and long-term growth. In this document, a system dynamics model was constructed to generate three time series index futures innovation (2014-2024) in Mexican firms: products, processes, and products-processes. The results indicate the existence of dynamic scaling behavior ansatz from Family-Viscek to roughness kinetics for a moving interface. Therefore, it is expected that the dynamics of innovation rates of manufacturing firms in the Mexico City and Mexico, is described and predicted by the standard Langevin equation. This can be a strong support for the Mexican government authorities are better able to analyze the impact of innovation policies, both locally and nationally.